2022
DOI: 10.2147/jaa.s369811
|View full text |Cite
|
Sign up to set email alerts
|

A Meta Analysis of Physical Exercise on Improving Lung Function and Quality of Life Among Asthma Patients

Abstract: Objective This paper aims to perform a systematic assessment of the influence of physical exercise on asthma patients and discuss the intervention effects of different exercises on the lung function FEV1 (%pred) and quality of life among asthma patients so as to lay a scientific foundation for improving asthma symptoms. Methods Both Chinese and English databases were retrieved, including PubMed, Web of Science, Embase, The Cochrane Library, CBM, CNKI, Wan Fang Data, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…In addition, this review did not analyze the data using the Asthma Quality of Life Questionnaire (AQLQ) of two studies (31,32) that were excluded without explanation. On the other hand, two other recent systematic reviews with meta-analysis showed a significant difference in favor of exercise in patients with asthma (33,34). (34) included nine studies in their meta-analysis and also demonstrated an improvement and reached the minimal clinically significant difference in QoL after aerobic exercise (AQLQ or pediatric AQLQ evaluated QoL).…”
Section: Quality Of Life (Qol)mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, this review did not analyze the data using the Asthma Quality of Life Questionnaire (AQLQ) of two studies (31,32) that were excluded without explanation. On the other hand, two other recent systematic reviews with meta-analysis showed a significant difference in favor of exercise in patients with asthma (33,34). (34) included nine studies in their meta-analysis and also demonstrated an improvement and reached the minimal clinically significant difference in QoL after aerobic exercise (AQLQ or pediatric AQLQ evaluated QoL).…”
Section: Quality Of Life (Qol)mentioning
confidence: 96%
“…On the other hand, two other recent systematic reviews with meta-analysis showed a significant difference in favor of exercise in patients with asthma (33,34). (34) included nine studies in their meta-analysis and also demonstrated an improvement and reached the minimal clinically significant difference in QoL after aerobic exercise (AQLQ or pediatric AQLQ evaluated QoL). The mechanisms involved in improving QoL may be associated with improvements in all domains of the AQLQ, including physical limitations, symptom frequency, socioeconomic conditions, and psychosocial health.…”
Section: Quality Of Life (Qol)mentioning
confidence: 96%
“…Besides, similar to the findings from the adolescent stage, a Cochrane review also reported the modest evidence on the improvement of quality of life among adults after 3‐months of breathing‐exercises, though high heterogeneity was identified across studies and dosage and types of breathing exercise sessions remained inconclusive 38 . Furthermore, a meta‐analysis study compared the beneficial impact of different types of exercise and revealed that aerobic exercises were more beneficial than free‐choice or combined types of exercise for lung function and quality of life among asthma patients 39 . Although evidence showed that high‐intensity interval training could reduce asthma symptoms during the chronic phase, 40 no conclusion has been given in existing reviews on the duration and intensity of exercise.…”
Section: Resultsmentioning
confidence: 99%
“…38 Furthermore, a meta-analysis study compared the beneficial impact of different types of exercise and revealed that aerobic exercises were more beneficial than free-choice or combined types of exercise for lung function and quality of life among asthma patients. 39 Although evidence showed that high-intensity interval training could reduce asthma symptoms during the chronic phase, 40…”
Section: Infancymentioning
confidence: 99%
“…Our findings could help provide patient education, one of the four essential components of asthma management, including monitoring symptoms and lung function, controlling triggering factors and comorbid conditions, and providing pharmacologic therapy [ 53 ]. Since asthma severity varies among people depending on socioeconomic, behavioral, and clinical characteristics, patient education and physical exercise are essential for decreasing asthma exacerbations and improving the control [ 54, 55 ]. Thus, expert panel reports three and Global Initiative for Asthma has described a stepwise treatment approach and strategy to prevent future risks of asthma onset [ 56 ].…”
Section: Discussionmentioning
confidence: 99%